2016
DOI: 10.1097/htr.0000000000000079
|View full text |Cite
|
Sign up to set email alerts
|

Objective and Subjective Burden of Informal Caregivers 4 Years After a Severe Traumatic Brain Injury: Results From the PariS-TBI Study

Abstract: Four years after a severe traumatic brain injury, 44% of ICs experienced a heavy multidimensional burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 67 publications
3
48
3
Order By: Relevance
“…In addition, burden increased more frequently among caregivers with a moderate-to-high as compared to a low burden at the 1-year follow-up. One study found no significant change in caregiver burden between 6 and 12 months post-injury (Marsh et al, 2002), whereas the PariS-TBI study found a decrease in burden at 4 as compared to 1 year (Bayen et al, 2014;Bayen et al, 2013). However, the latter investigators did not compare the same population at the two time points; this along with the longer time span post-injury and differences in analytical approaches could explain the discrepancy between their results and ours.…”
Section: Caregiver Burdencontrasting
confidence: 54%
See 2 more Smart Citations
“…In addition, burden increased more frequently among caregivers with a moderate-to-high as compared to a low burden at the 1-year follow-up. One study found no significant change in caregiver burden between 6 and 12 months post-injury (Marsh et al, 2002), whereas the PariS-TBI study found a decrease in burden at 4 as compared to 1 year (Bayen et al, 2014;Bayen et al, 2013). However, the latter investigators did not compare the same population at the two time points; this along with the longer time span post-injury and differences in analytical approaches could explain the discrepancy between their results and ours.…”
Section: Caregiver Burdencontrasting
confidence: 54%
“…The French PariS-TBI study reported a decrease in caregiver burden from 1 to 4 years post-injury (Bayen et al, 2014;Bayen et al, 2013). Among 57 caregivers of patients with severe TBI, the perceived level of burden was high at the 3-, 6-and 12-months follow-up times, with a slight increase between 6 and 12 months (M. G. Livingston et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The work associated with living with TBI in the community is multi-faceted and potentially burdensome (i.e., workload) [16,17]. Several factors impact this workload, including the complexity of TBI, which is unique to each person [18].…”
Section: Introductionmentioning
confidence: 99%
“…It may vary according to the degree of severity of functional disorder and the patients' autonomy in ADL. [16][17][18][19] Family members of patients with ABI often report poor family functioning, which does not improve with time. [20][21][22] Supporting families of patients with ABI may include various interventions modalities, such as support groups for family members of patients requiring intensive care, communication interventions, and/or flexible visiting hours.…”
Section: Introductionmentioning
confidence: 99%